2022
DOI: 10.1155/2022/6120908
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Risk Factors of Retinal Diseases among Patients in Madang Province, Papua New Guinea

Abstract: Purpose. To explore the prevalence of risk factors of retinal diseases among patients seeking services from Madang Provincial Hospital Eye Clinic in Papua New Guinea. Materials and Methods. A hospital-based retrospective study was conducted at the only eye clinic serving the entire Madang province of Papua New Guinea. Purposive sampling was used to obtain data from patients’ record cards at the eye clinic from January to June 2021. The data collected included gender, age, presenting visual acuity, blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The adult patients in this study recorded large numbers of corneal ulcers and keratitis and refractive error as the main ocular problems ( Table 4 ). In Madang and PNG, most of the people conduct their daily activities in an open environment engaging in farming ( 16 , 36 ), trading ( 36 ), welding and carpentry without using protective eyewear. In addition, tribal conflicts and domestic violence are common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adult patients in this study recorded large numbers of corneal ulcers and keratitis and refractive error as the main ocular problems ( Table 4 ). In Madang and PNG, most of the people conduct their daily activities in an open environment engaging in farming ( 16 , 36 ), trading ( 36 ), welding and carpentry without using protective eyewear. In addition, tribal conflicts and domestic violence are common.…”
Section: Discussionmentioning
confidence: 99%
“…In Papua New Guinea (PNG), a rapid assessment of avoidable blindness (RAAB) was carried out in 2017 but the study focused mainly on the causes of visual impairment (VI) and blindness (presenting visual acuity <6/12) in the older population (aged 50 years and older) ( 14 ). Contrariwise, studies have indicated that there are potentially blinding conditions that do not present significant ocular or visual symptoms in the initial stages ( 11 , 15 ), and PNG is not immune to such potential causes of visual impairment ( 16 , 17 ). Therefore, the findings of the RAAB are limited in terms of the general presentation of eye disorders in the country.…”
Section: Introductionmentioning
confidence: 99%
“…A recent finding indicated that 50% of all ophthalmic patients aged ≥30 years who visited the MPHEC in the first half of 2021 were either pre-diabetic or diabetic [13]; hence, it was paramount that they undergo DR screening. Despite the availability of the free retinal screening service at the facility, the uptake of the service has been very low, at an average of two patients per month for the years 2017 to 2021.…”
Section: Introductionmentioning
confidence: 99%